Pola Distribusi Perdagangan dan MPP (Margin Pengangkutan dan Perdagangan) Bawang Merah di Jawa Barat - Zahra Nur Safa; Euis Dasipah; Dety Sukmawati (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The trade distribution pattern describes the distribution chain of a commodity from the producer to the final consumer in an area where trading activities occur. The distribution of shallot commodities from final consumers involves one to seven trading business actors. The seven business actors can be broken down into six distribution patterns. Every business actor gets a transportation and trade margin (MPP) in his trading business, the longer the distribution chain, the potential for price increases for consumers. Farmers know the sources of price information from large farmers, collectors, and wholesalers. The distribution pattern in West Java Province consists of six patterns carried out by seven subjects, namely collectors, distributors, sub-distributors, agents, wholesalers, retailers, and supermarkets/supermarkets. This study took samples from shallot production centers in West Java, which is one sub-district which has the largest area and largest production. The number of farmers who became respondents was 10 percent, with the category of having been trying to cultivate shallots for at least three years which was analyzed descriptively. Based on the survey results, the MPP of shallots in West Java Province is 31.37 percent where the increase in the price of shallots from farmers to final consumers in West Java Province is 31.37 percent.